Creative Relationships: A Basic Concept within Entrepreneurship Education? - Aspelin, Jonas (Senate Hall, 2015)
This article outlines a concept termed "creative relationships" which ultimately could be used as basic concept and discursive tool in entrepreneurship education. A specifying distinction between "creative co-operation" and "creative co-existence" is also tentatively introduced, and it is argued that both these aspects need to be recognized in the discourse. The concept "creative relationships" is built on a review and an analysis of three distinct relational conceptions of creativity; Hannah Arendt's, Kenneth Gergen's and Martin Buber's. A main point of the analysis is that the concept of creativity, as well as its broader counterpart, entrepreneurship, is not comprehensible without recognizing its relational context. At the end of the article, the outlined concept is applied to the question of curriculum development in entrepreneurship education. Keywords: entrepreneurship education, creativity, relationship, creative relationships, Arendt, Gergen, Buber
Keywords: entrepreneurship education|creativity|relationship|creative relationships|Arendt|Gergen|Buber